Role and molecular mechanism of heterogeneous nuclear ribonucleoprotein K in tumor development and progression - LU, JING (Biomed Rep, 2016)
Heterogeneous nuclear ribonucleoprotein K (hnRNP K) is a member of the hnRNP family, which exists in the nucleus and the cytoplasm simultaneously. It is a multifunctional protein that can participate in a variety of regulatory progressions of gene expression and signal transduction, such as chromatin remodeling, transcription, RNA alternative splicing and translation. hnRNP K not only directly binds to the kinases, but also recruits the associated factors regarding transcription, splicing and translation to control gene expression, and therefore, it serves as a docking platform for integrating transduction pathways to nucleic acid-directed processes. Numerous studies also show that abnormal expression of hnRNP K is closely associated with the tumor formation. This protein is overexpressed in numerous types of cancer and its aberrant cytoplasmic localization is also associated with a worse prognosis for patients. These results consistently indicate that hnRNP K has a key role in cancer progression. To understand the hnRNP K pathophysiological process in tumor disease, the previous research results regarding the association between hnRNP K and tumors were reviewed.